Shikhara of the Kaner-ki-Pulti Temple - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the Kaner-ki-Pulti Temple is severely damaged. While the lower part remains intact, the upper section has completely collapsed. A detailed examination of the shikhara reveals that it is of the Bhumija style, featuring latas (central offsets) in the cardinal directions. Between these latas, rows of kutas (miniature shikharas) are arranged. The central offset is plain at its base and adorned with a decorated pediment above. The remaining portion of the lata is intricately carved with chaitya arch (dormer window) jala. The spaces between the latas are filled with two rows of kutastambhas (vertical rows of miniature shikharas).